Static magnetic field coupled with magnetic biochar boosts methane production in sludge anaerobic digestion by activating dual electron transfer mechanisms - Likui Feng; Muzi Li; Kaiyi Zhang; Shuo Liu; Heng Liang; Zhelu Gao; Huizhi Mu; Shufei He; Qingliang Zhao; Liangliang Wei (Journal of Environmental Chemical Engineering, 2026)

Upcycling hazardous electric arc furnace dust into defect-rich ZnO/ZnFe2O4 heterojunction for in situ H2O2 electrogeneration and water purification - Lijuan Jia; Bo Liu; Guoxing Mu; Yiqiang Ji; Fang Wang; Rui Cao; Ping Ning; Shuo Cui; Jiayu Feng (Chemical Engineering Journal, 2026)

Rapid colorimetric assay-guided discovery of α-glucosidase inhibitors from natural products using a MOF-818@Pt nanozyme - Baiting Zhang; Mu Chen; Yang Huang; Siyi Mou; Shulei Qin; Shuo Yang; Zhengjin Jiang; Shengfeng Huang (Analytica Chimica Acta, 2026)

Experimental and Numerical Study on Dynamic Response of PVC Foam Sandwich Beams Under Ice Impact - Kailing Guo; Juncheng Chen; Wei Cai; Shuo Zhou; Mengying Mu (Journal of Marine Science and Engineering, 2026)
This paper mainly investigates the ice-impact resistance of PVC foam sandwich beams for polar ship protective structures through low-velocity impact experiments and nonlinear finite element simulations. An experimentally validated elastic–plastic coupled model, accounting for ice crushing and large structural deformation, was used to examine the effects of core density and face-sheet thickness distribution on the ice-impact response of sandwich beams. Results show that the upper face sheet undergoes local indentation and global bending, the lower face sheet mainly bends globally, and the foam core exhibits local compression and overall bending, while compressive deformation accompanied by ice crushing and spalling occurs at the front part of the ice impactor. Moreover, the effective structural stiffness decreased during plastic loading as local indentation and core compression developed, whereas the unloading stiffness was higher than the effective stiffness during plastic loading. Energy dissipation primarily comes from ice crushing, face-sheet plasticity, and core compression. Increasing core density reduces deflection and core compression but increases peak force. Among the three face-sheet configurations examined at a constant total thickness, the configuration with a thinner upper face sheet and a thicker lower face sheet produced a smaller final deformation of the lower face sheet. This study provides a useful reference for ice-resistant design of sandwich structures in polar ships.

An ovarian follicle-based angiogenesis microphysiological system for high-efficiency screening of anti-angiogenic drugs - Xuebing Yang; Jing Liang; Nan Sun; Lu Mu; Jinfeng Xiong; Ge Wang; Kaiying Geng; Xie’an Feng; Yibo Wang; Shuo Zhang; Xueqiang Xu; Yan Zhang; et al. (Science Bulletin, 2026)

Corrigendum to ‘ORF603 derived from AcMNPV plays entirely opposite roles in regulating BmNPV infection’ [Pesticide Biochemistry and Physiology 220 (2026) 107056] - Xin-yi Ding; Jiang-zhi Su; Yu-shuo Song; Wen-Jing Yu; Zuo-min Shao; Sheng Qin; Xia Sun; Xue-yang Wang; Xiao-mei Ma; Mu-wang Li (Pesticide Biochemistry and Physiology, 2026)

ORF603 derived from AcMNPV plays entirely opposite roles in regulating BmNPV infection - Xin-yi Ding; Jiang-zhi Su; Yu-shuo Song; Wen-Jing Yu; Zuo-min Shao; Sheng Qin; Xia Sun; Xue-yang Wang; Xiao-mei Ma; Mu-wang Li (Pesticide Biochemistry and Physiology, 2026)

Waste valorization of magnesium slag via iron modification: Synergistic removal of Fe and Mn from acid mine drainage and underlying removal mechanisms - Liping Zhang; Lifang Wang; Siying Liu; Weiwei Wang; Huitong Li; Ran Mu; Shuo Chen; Runchao Sun (Journal of Water Process Engineering, 2026)

High-value utilization of hazardous solid waste for efficient electrocatalytic oxygen reduction to produce hydrogen peroxide - Bo Liu; Xiaoshuang Song; Guoxin Mu; Jiayu Feng; Fang Wang; Rui Cao; Zibin Pan; Feixiang Lu; Ping Ning; Shuo Cui; Lijuan Jia (Environmental Research, 2026)

Study on plasma-activated supersonic water fog atomization and dust suppression performance - Mu Xinsheng; Ge Shaocheng; Zhang Tian; Jing Deji; Liu Shuo; Sun Liying; Pang Xingyu (Process Safety and Environmental Protection, 2026)

FM-SAM: individual tree crown delineation and classification based on Segmentation Anything Model (SAM) and YOLOv10 in UAV imagery for forest monitoring - Haohua Que; Haojia Gao; Weihao Shan; Mingkai Liu; Jianshuo An; Fei Deng; Shuo Feng; Xinghua Yang; Lei Mu (Computers and Electronics in Agriculture, 2026)

Corrigendum to “A carboxymethyl chitosan/trans-2-hexenal Schiff's base gel with controlled density using dynamic imine bonds: pH-controlled release and extended duration” [Carbohydrate Polymers 354 (2025) 123305] - Guang-shuo Zhou; Tao Zhang; Yan Jin; Guo-fu Zhang; Bo Kong; Da-yin Chen; Guo-xian Wang; Zi-shu Wang; Meng-ying Qi; Da-xia Zhang; Wei Mu; Nan Zou (Carbohydrate Polymers, 2026)

UV-resistant, antibacterial, antioxidant, and biodegradable alizarin/curcumin-based pH indicator film for monitoring shrimp freshness - Yanhong Liu; Xiwang Mu; Zechen Liu; Hongyu Qian; Lingling Zhang; Guangrao Chen; Shuo Wang (Food Research International, 2025)

Integration LC-MS/MS and molecular modeling techniques to elucidate the molecular mechanisms of goat whey protein-IgG interactions - Hongbo Li; Quan Gao; Xianjun Gao; Geng Long; Meng Bian; Shuo Feng; Shanbo Mu; Hongjuan Li; Jinghua Yu (Food Chemistry, 2025)

Preparation of mesoporous carbon/clay composite adsorbent based on the mixed-dimension attapulgite: Dye adsorption, mechanism and molecular dynamics calculations - Shuo Wang; Yuan Zhang; ChengHui Lan; ChaoXi Mu; JianGuo Liu; MengYao Wang; Bin Mu (Journal of Environmental Chemical Engineering, 2025)

Effects of tank color on the survival, growth performance and carapace color of juvenile mud crab (Scylla paramamosain) - Xinyue Liu; Shujian Chen; Shuo Wang; Kaijia Yu; Yangfang Ye; Ronghua Li; Changkao Mu; Chunlin Wang; Ce Shi (Aquaculture, 2025)

Alternative splicing of OsNPR3 promoted by the bacterial TAL effectors-targeted splicing regulator OsRBP11 antagonizes OsNPR1 function and enhances disease susceptibility in rice - Xiaochen Chen; Xiaohui Yao; Fang Yan; Shaofang Li; Zuo-Dong Wang; Fu-You Yin; Miao Zhou; Zhen Wang; Lina Qin; Baoguo Zhao; Kai Lu; Liyuan Zhang; et al. (Molecular Plant, 2025)

The emulsion-filled gels with different fat contents exhibit various friction behavior and dynamic fat-related texture perception at different temperatures - Yueji Zeng; Sihan Zhang; Ke Fan; Shuo Mu; Yang Luo; Linlin Wang; Xiankang Fan; Fuqing Wang; Ran Wang; Jie Luo (Food Quality and Preference, 2025)

Smart temperature sensors based on flexible CB/TPU/ PVDF membranes for eliminating pressure interference - Shuo Li; Jiaxin Sun; Feng Tong; Guo Chen; Zhefu Mu; Xiaoqiang Zhang; Sheng Huang; Zheng Chen; Lei Xu; Changyun Li; Peng Wang; Xiuquan Gu (Chemical Engineering Journal, 2025)

A carboxymethyl chitosan /trans-2-hexenal Schiff's base gel with controlled density using dynamic imine bonds: pH-controlled release and extended duration - Guang-shuo Zhou; Tao Zhang; Yan Jin; Guo-fu Zhang; Bo Kong; Da-yin Chen; Guo-xian Wang; Zi-shu Wang; Meng-ying Qi; Da-xia Zhang; Wei Mu; Nan Zou (Carbohydrate Polymers, 2025)

Extraction of betalaine from red pitaya peel using deep eutectic solvent and its research in films - Yanhong Liu; Xiwang Mu; Hui Wang; Mingyue Wang; Lingling Zhang; Guangrao Chen; Shuo Wang (Food and Bioproducts Processing, 2025)

Fabrication of chitosan-based smart film by the O/W emulsion containing curcumin for monitoring pork freshness - Yanhong Liu; Guangrao Chen; Yajiao Yang; Ruonan Wu; Lingling Zhang; Xiwang Mu; Shuo Wang (Journal of Food Engineering, 2024)

Monovalent cation exchange membranes prepared by Fe3+-assisted coupled surface modification of PEI-PPy for potassium extraction from simulated brine - Mengmeng Sun; Chenglin Mu; Shuo Wang; Jingtao Bi; Xiaofu Guo; Shizhao Wang; Yingying Zhao (Desalination, 2024)

Effects of miR-204-5p and Target Gene EphB2 on Cognitive Impairment Induced by Aluminum Exposure in Rats - Wei Liu; Jie Gao; Niping Hao; Jing Li; Jing Pei; Danfeng Zou; Shuo Yang; Yuhua Yin; Xiaoming Yang; Ping Mu; Lifeng Zhang (Biological Trace Element Research, 2024)

High-density mapping of durable and broad-spectrum stripe rust resistance gene Yr30 in wheat - Xiaoting Wang; Mingjie Xiang; Huaizhou Li; Xiaoxiao Li; Keqing Mu; Shuo Huang; Yibo Zhang; Xiangrui Cheng; Shuqing Yang; Xunying Yuan; Ravi P. Singh; Sridhar Bhavani; et al. (Theoretical and Applied Genetics, 2024)

Perfect cooperative pest control via nano-pesticide and natural predator: High predation selectivity and negligible toxicity toward predatory stinkbug - Shangyuan Wu; Qinhong Jiang; Zhilin Xia; Zhirong Sun; Qing Mu; Chunyang Huang; Fan Song; Meizhen Yin; Jie Shen; Hu Li; Shuo Yan (Chemosphere, 2024)

Enhanced Beta2-band Oscillations Denote Auditory Hallucination in Schizophrenia Patients and a Monkey Model of Psychosis - Shuo Ma; Tianzhen Chen; Wenjun Jia; Jie Liu; Shihan Ding; Puzhe Li; Hong Gan; Dapeng Zhang; Shuxin Shao; Mu-Ming Poo; Min Zhao; Bomin Sun; et al. (Neuroscience Bulletin, 2024)

A New Plastic Design Approach for the Vertical-Side-Plating Thickness of Ice-Strengthened Ships Suffering from Ice Floe Impacts - Mengying Mu; Kailing Guo; Wei Cai; Ling Zhu; Zhenyu Pi; Shuo Zhou (Journal of Marine Science and Engineering, 2024)
Ice-strengthened ships inevitably suffer from ice floe impacts during navigation in icy regions. Under some extreme-ice-impact loadings, the ship structure will experience plastic deformations. The magnitude of plastic deformation is highly correlated with the ice floe-impact energy level. During most ice impacts, only the ship’s plate undergoes minor plastic deformation. Considering that the structure still has a high structural strength with a minor permanent deformation, developing a structural plastic design method for polar ships has become a hot research issue in current studies. Therefore, in this paper, based on the rigid-plastic theory and the ice-crushing-energy approach, an experimentally verified theoretical model for predicting plastic deformations of the vertical-side plate of polar ship subjected to ice floe impacts was established. According to the analytical solutions of the plastic deformation, the plastic design formula to determine the plating thickness of ice-strengthened ships subjected to ice floe impacts was further derived based on the plastic design criteria. In addition, the parameter analysis of ice strength described by the ice pressure–area relationship, allowable-permanent-set parameter, impact energy and ice shape were conducted, and plating-thickness design curves with different design parameters were given. The design of plating thickness is very sensitive to the determinations of the allowable-permanent set and ice pressure–area curves. The designed plating thickness decreased with the increase of the allowable-permanent set. Moreover, a comparative analysis of the designed plating thickness for ice floe impact and rigid-mass impact was also carried out. Under the same impact conditions, due to energy absorption caused by ice damage, the designed thickness of the plate for rigid-mass impact was much larger than that for the ice impact. It is necessary to consider the impact-induced ice damage and energy dissipation in a structural design, instead of using rigid impact loads for conservative design. The research in this paper can provide some useful references for the structural design of ice-strengthened ships subject to ice floe impacts.

How volatile composition facilitates olfactory discrimination of fat content in beef and pork - Shuo Mu; Nan Ni; Yuting Zhu; Sanne Boesveldt; Markus Stieger (Food Research International, 2023)

Smells like fat: A systematic scoping review on the contribution of olfaction to fat perception in humans and rodents - Matjaž Pirc; Shuo Mu; Gino Frissen; Markus Stieger; Sanne Boesveldt (Food Quality and Preference, 2023)

Quantifying soil nitrous oxide emissions in spring freezing-thawing period over different vegetation types in Northeast China - Bin Wu; Chang-cheng Mu; Hui Liu; Ya-kun Xu; Yue Zhang; Jia-shuo Yang; Wen-nian Xu (Journal of Mountain Science, 2022)

Description of Lujinxingia vulgaris sp. nov., isolated from coastal sediment via prey-traps - Shuo Wang; Da-Shuai Mu; Guang-Yu Li; Zong-Jun Du (Antonie van Leeuwenhoek, 2021)

Low-Se Diet Can Affect Sperm Quality and Testicular Glutathione Peroxidase-4 activity in Rats - Qin Wang; Shuo Zhan; Yiqun Liu; Feng Han; Lili Shi; Chao Han; Weipeng Mu; Jizhong Cheng; Zhen-wu Huang (Biological Trace Element Research, 2021)

Lacustrine carbonates of Paleogene in Zhanhua Sag, Bohai Bay Basin, East China - Shuo Yi; Wenhui Huang; Nana Mu (Carbonates and Evaporites, 2019)

A major QTL co-localized on chromosome 6BL and its epistatic interaction for enhanced wheat stripe rust resistance - Qingdong Zeng; Jianhui Wu; Shengjie Liu; Shuo Huang; Qilin Wang; Jingmei Mu; Shizhou Yu; Dejun Han; Zhensheng Kang (Theoretical and Applied Genetics, 2019)

Genetic architecture of wheat stripe rust resistance revealed by combining QTL mapping using SNP-based genetic maps and bulked segregant analysis - Jingmei Mu; Shuo Huang; Shengjie Liu; Qingdong Zeng; Miaofei Dai; Qilin Wang; Jianhui Wu; Shizhou Yu; Zhensheng Kang; Dejun Han (Theoretical and Applied Genetics, 2019)

Comparative genome-wide mapping versus extreme pool-genotyping and development of diagnostic SNP markers linked to QTL for adult plant resistance to stripe rust in common wheat - Jianhui Wu; Shuo Huang; Qingdong Zeng; Shengjie Liu; Qilin Wang; Jingmei Mu; Shizhou Yu; Dejun Han; Zhensheng Kang (Theoretical and Applied Genetics, 2018)

SNP-based pool genotyping and haplotype analysis accelerate fine-mapping of the wheat genomic region containing stripe rust resistance gene Yr26 - Jianhui Wu; Qingdong Zeng; Qilin Wang; Shengjie Liu; Shizhou Yu; Jingmei Mu; Shuo Huang; Hanan Sela; Assaf Distelfeld; Lili Huang; Dejun Han; Zhensheng Kang (Theoretical and Applied Genetics, 2018)

Rapid identification of an adult plant stripe rust resistance gene in hexaploid wheat by high-throughput SNP array genotyping of pooled extremes - Jianhui Wu; Shengjie Liu; Qilin Wang; Qingdong Zeng; Jingmei Mu; Shuo Huang; Shizhou Yu; Dejun Han; Zhensheng Kang (Theoretical and Applied Genetics, 2018)

Rational Improvement of Peptide Affinity to Human Pregnancy-Related Serine Protease HtrA3 PDZ Domain by Introducing a Halogen Bond to the Domain–Peptide Complex Interface - Hong Liu; Shuo-Fen Dou; Xue Zhang; Yan Wang; Qing-Li Wen; Ya-Nan Mu (International Journal of Peptide Research and Therapeutics, 2016)

Development and characterization of a mouse floxed Bmp2 osteoblast cell line that retains osteoblast genotype and phenotype - Li-an Wu; Junsheng Feng; Lynn Wang; Yan-dong Mu; Andrew Baker; Kevin J. Donly; Stephen E. Harris; Mary MacDougall; Shuo Chen (Cell and Tissue Research, 2011)

Isolation and characterization of a novel thermophilic Bacillus strain degrading long-chain n-alkanes - Lei Wang; Yun Tang; Shuo Wang; Ru-Lin Liu; Mu-Zhi Liu; Yan Zhang; Feng-Lai Liang; Lu Feng (Extremophiles, 2006)